IMPACT OF ACTIVE IMMUNIZATION AGAINST INHIBIN, USING A SINGLE BOOSTER DOSE, ON OVULATION RATE AND FERTILITY IN LOW-PROLIFIC SIROHI GOATS - PRIYADHARSINI, R; KHARCHE, S D; GOEL, A K; JINDAL, S K; KUMAR, S (The Indian Journal of Animal Reproduction, 2022)
Five Sirohi does received primary immunization against endogenous inhibin (400 μg peptide-ovalbumin conjugate, S.C.) and five others were kept as control (400 μg ovalbumin, S.C.). All the does received a single booster (Immunized, 200 μg peptide-ovalbumin conjugate; control, 200 μg ovalbumin) about four weeks after primary immunization. Estrus was synchronized using a double injection schedule of PGF2α on days 35 and 45 from the day of primary immunization. Immunization against inhibin lead to an increase in ovulation rate and corpora lutea as indicated by plasma progesterone. The kidding percentage in immunized and control group was 100% (litter size, 1.63) and 80% (litter size, 1.25), respectively. Thus, inhibin immunization with a single booster dose can be used to improve ovarian activity and fertility in low-prolific Sirohi goats.